Transcending the Nature of Refinement: The Policy Development on Liberal Arts Education in China. Issue 3 (4th May 2017) - Jiang, You Guo; Guo, Hong
Abstract: Liberal arts education is based on a philosophy that uses an interdisciplinary curriculum to cultivate critical thinking, creativity, moral reasoning, analytical skills, and a sense of social responsibility. As China continues to invest in higher education, faculty, administrators and policy makers are aware that a narrow focus on professional and scientific training is insufficient to enable students to meet today's global needs and challenges. Through qualitative and quantitative research and document analysis, this article examines Chinese policy development and transformation regarding higher education and liberal arts education in general, and the current state of liberal arts education in three universities in Shanghai in particular.